Shine your light: The life and lessons of Madeline Woleg - Naomi Sunderland (13213455); Phil Graham (10841754); Joel Spence (13226742); Rae Cooper (12827099); Kayla Harris (13226745) (2021)
This output is part of a suite of self-published, peer reviewed community and creative resources from the Australian Research Council funded Remedy Project: First Nations music as a determinant of health